2012
DOI: 10.1890/11-1861.1
|View full text |Cite
|
Sign up to set email alerts
|

What is the form of the productivity–animal‐species‐richness relationship? A critical review and meta‐analysis

Abstract: The nature of the relationship between productivity and species richness has remained controversial for at least two decades. Recently authors have favored the suggestion that the form of this relationship is highly variable and scale dependent. However, this conclusion is not universally accepted. Here we present the results of a meta-analysis of animal productivity-species-richness relationships (PSRR) in terrestrial and freshwater ecosystems. Initially, 374 separate cases from 273 published studies were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 48 publications
4
97
0
Order By: Relevance
“…In Lake Jinghu, the TP was between 0.02 and 0.11 mg.L −1 , and indices of species diversity showed a positive correlation with phosphorus concentration (TP and/or PO 4 3− ). The ecological effects of phosphorus on rotifer zooplankton species diversity are still debatable, and have been focused on identifying a positive (productivity increases diversity) or unimodal relationship between the two (low diversity at the lower and upper extremes of productivity) 50–53 . Our findings were in agreement with the established result that zooplankton diversity in reservoirs is positively correlated with TP and that productive environments (natural lakes) gather more species 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In Lake Jinghu, the TP was between 0.02 and 0.11 mg.L −1 , and indices of species diversity showed a positive correlation with phosphorus concentration (TP and/or PO 4 3− ). The ecological effects of phosphorus on rotifer zooplankton species diversity are still debatable, and have been focused on identifying a positive (productivity increases diversity) or unimodal relationship between the two (low diversity at the lower and upper extremes of productivity) 50–53 . Our findings were in agreement with the established result that zooplankton diversity in reservoirs is positively correlated with TP and that productive environments (natural lakes) gather more species 54 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of empirical studies of the productivity-species richness relation published in 1999 suggested that monotonous and unimodal relationships were about equally frequent (116). However, a 2012 meta-analysis (117) concluded that earlier studies had misclassified many case studies as unimodal and suggested that if correct attribution methods were used and only robust studies were included, monotonous productivity-species richness relationships prevail at all scales.…”
Section: Hanpp and Biodiversitymentioning
confidence: 99%
“…Vegetation indices are often used as a surrogate for plant productivity (Cusens et al, 2012), and EVI was developed to optimize the vegetation signal with improved sensitivity in high biomass areas (Huete et al, 2002). I downloaded EVI from http://daac.ornl.gov, at a spatial resolution of 250 m, and calculated its mean value between years 2000 and 2013.…”
Section: Climatic Variablesmentioning
confidence: 99%